The totalitarian worlds of Merry Cemetery by Vasyl Stus and Little Apocalypse by Tadeusz Konwicki: differences and similarities - Mychajłowa, Tetiana (Poznańskie Studia Slawistyczne, 2025)
The article is devoted to a comparative analysis of totalitarian worlds in Ukrainian and Polish literature based on the material of works published in the underground circulation and written in complete freedom from censorship restrictions (taking into account Konwicki’s earlier novel Ascension). Numerous typological similarities are revealed (queues, poverty, falsehood, the motif of self-immolation as an extreme form of protest, etc.), differences in the description of totalitarian reality by the writers are noted, and the features of the author’s individuality in presenting national issues are emphasized.